Monocyte to High-Density Lipoprotein Cholesterol Ratio at the Nexus of Type 2 Diabetes Mellitus Patients With Metabolic-Associated Fatty Liver Disease - Jia, Jue; Liu, Ruoshuang; Wei, Weiping; Yu, Fan; Yu, Xiawen; Shen, Yirong; Chen, Caiqin; Cai, Zhensheng; Wang, Chenxi; Zhao, Zhicong; Wang, Dong; Yang, Ling; et al. (Frontiers in Physiology, 2021)
Background: Recently, monocyte to high-density lipoprotein cholesterol ratio (MHR) as a novel inflammatory biomarker has drawn lots of attention. This study was conducted in patients with type 2 diabetes mellitus (T2DM) to investigate the correlation between MHR and metabolic‑associated fatty liver disease (MAFLD). Methods: Totally, 1051 patients with T2DM from the Affiliated Hospital of Jiangsu University were enrolled and classified as MAFLD (n=745) group and non-MAFLD (n=306) group according to the MAFLD diagnostic criteria. On the other hand, patients were also separated into four groups based on MHR quartiles. Anthropometric and biochemical measurements were made. Participants’ visceral fat area (VFA) and subcutaneous fat area (SFA) were measured by dual bioelectrical impedance. Fatty liver was assessed by ultrasonography. Results: MHR level of subjects in MAFLD group was statistically greater than that in non-MAFLD group (P < 0.05). Meanwhile, MHR was higher in overweight or obese MAFLD group compared with that in lean MAFLD group (P < 0.05). The AUC assessed by MHR was larger than that of other inflammatory markers (P < 0.01). The cut-off value of MHR was 0.388, with a sensitivity of 61.74% and a specificity of 56.54%. For further study, binary logistic regression analyses of MAFLD as a dependent variable, the relationship between MHR and MAFLD was significant (P < 0.01). After adjusted many factors, the relationship still existed. In the four groups based on MHR quartiles, groups with higher values of MHR had significant higher prevalence of MAFLD (P < 0.05). The percentages of obese MAFLD patients increased as MHR level increased (P < 0.01). Among different quartiles of MHR, it showed that with the increasing of MHR, the percentages of MAFLD patients who had more than four metabolic disfunction indicators increased, which was 46.39%, 60.52%, 66.79% and 79.91% respectively in each quartile. Conclusion: MHR is a simple and practicable inflammatory parameter that could be used for assessing MAFLD in T2DM. T2DM patients with higher MHR have more possibility to be diagnosed as MAFLD. Therefore, more attention should be given to the indicator in the examination of T2DM.